High-Sensitivity Troponin T and Mortality After Elective Percutaneous Coronary Intervention - Ndrepepa, Gjin; Colleran, Roisin; Braun, Siegmund; Cassese, Salvatore; Hieber, Julia; Fusaro, Massimiliano; Kufner, Sebastian; Ott, Ilka; Byrne, Robert A.; Husser, Oliver; Hengstenberg, Christian; Laugwitz, Karl-Ludwig; et al. (Journal of the American College of Cardiology, 2016)
Background The prognostic value of high-sensitivity troponin T (hs-TnT) elevation after elective percutaneous coronary intervention (PCI) in patients with or without raised baseline hs-TnT levels is unclear. Objectives The goal of this study was to assess whether the prognostic value of post-procedural hs-TnT level after elective PCI depends on the baseline hs-TnT level. Methods This study included 5,626 patients undergoing elective PCI who had baseline and peak post-procedural hs-TnT measurements available. The primary outcome was 3-year mortality (with risk estimates calculated per SD increase of the log hs-TnT scale). Results Patients were divided into 4 groups: nonelevated baseline and post-procedural hs-TnT levels (hs-TnT ≤0.014 μg/l; n = 742); nonelevated baseline but elevated post-procedural hs-TnT levels (peak post-procedural hs-TnT >0.014 μg/l; n = 2,721); elevated baseline hs-TnT levels (hs-TnT >0.014 μg/l) with no further rise post-procedure (n = 516); and elevated baseline hs-TnT levels with a further rise post-procedure (n = 1,647). A total of 265 deaths occurred: 6 (1.6%) in patients with nonelevated baseline and post-procedural hs-TnT levels; 54 (3.8%) in patients with nonelevated baseline but elevated post-procedural hs-TnT levels; 50 (16.0%) in patients with elevated baseline hs-TnT levels with no further rise post-procedure; and 155 (18.2%) in patients with elevated baseline hs-TnT levels with a further rise post-procedure (p < 0.001). After adjustment, baseline hs-TnT levels (hazard ratio [HR]: 1.22; 95% confidence interval [CI]: 1.09 to 1.38; p < 0.001) but not peak post-procedural hs-TnT levels (HR: 1.04; 95% CI: 0.85 to 1.28; p = 0.679) were associated with an increased risk of mortality. Peak post-procedural hs-TnT findings were not associated with mortality in patients with nonelevated (HR: 0.93; 95% CI: 0.69 to 1.25; p = 0.653) or elevated (HR: 1.24; 95% CI: 0.91 to 1.69; p = 0.165) baseline hs-TnT levels. Conclusions In patients with coronary artery disease undergoing elective PCI, an increase in post-procedural hs-TnT level did not offer prognostic information beyond that provided by the baseline level of the biomarker.
CRIS-Team Scopus Importer:2023-03-08
Keywords: angina; biomarkers; coronary artery disease; coronary stenosis; prognosis; risk factors; stable